1991
DOI: 10.1111/j.1600-0722.1991.tb01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition of crevicular fluid before and after treatment

Abstract: Grevicular fluid (GF) analysis is a potential tool for site-speciflc diagnosis of periodontal disease activity. In this study, GE was collected using a novel washing method from 91 sites in 18 adult periodontitis patients both before and after conventional periodontal treatment. The sites studied were classified according to their clinical status and the number of polymorphonuclear leukocytes (PMN's) in GE samples. GF proteins were analyzed from individual sites with gel electrophoresis (SDS-PAGE). Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Although the outer fluid after dialysis would be rich in lower molecular mass components, outer membrane protein levels were not affected (data not shown). It has been suggested that the appearance of low molecular mass proteins in crevicular fluid is associated with the periodontal inflammatory status [33]. Moreover, asaccharolytic P. gingivalis has been known to utilize mainly peptides instead of single amino acids [21,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the outer fluid after dialysis would be rich in lower molecular mass components, outer membrane protein levels were not affected (data not shown). It has been suggested that the appearance of low molecular mass proteins in crevicular fluid is associated with the periodontal inflammatory status [33]. Moreover, asaccharolytic P. gingivalis has been known to utilize mainly peptides instead of single amino acids [21,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…It is present in inflammatory exudates (19,20), gingival crevicular fluid (24,25), and dentinal fluid (26). Its concentration in plasma is between 3.5% and 5% and up to 4% in inflammatory exudate (36).…”
Section: Discussionmentioning
confidence: 97%
“…Albumin is the main protein in human serum, and it is also a major component of inflammatory exudate (22,23). Its presence in gingival crevicular fluid and in the fluid from dentinal tubules has also been reported (24)(25)(26). In this study, the effect of bovine serum albumin on the antibacterial activity of NaOCl against four different microorganisms was investigated.…”
mentioning
confidence: 95%
“…Such additional in vitro investigations might include: (1) Monitoring degradation in a crevicular fluid like solution. Crevicular fluid contains high amounts of albumin 65, 66. A study by Çatiker et al67 showed that the hydrolytic breakdown of PLGA is strongly influenced by the presence of BSA as it increases the initial velocity of the hydrolytic de‐esterification process of glycolic‐acid containing copolymer.…”
Section: Discussionmentioning
confidence: 99%